MAIN DIRECTIONS FOR IMPROVING THE LEGAL BASIS OF THE SOCIAL PROTECTION SYSTEM IN THE REPUBLIC OF UZBEKISTAN - Shokirova - Inomjonova Mashkhurakhon Gayratjon qizi (Modern American Journals, 2025)
The social protection system plays an important role in ensuring the social, economic, and legal interests of citizens. Social services, subsidies, and benefits provided by the state are aimed at socially vulnerable groups of society. This article examines the main features of improving the legal framework of the social protection system in our country.
Keywords: Social protection, registry, social equality, privilege, preference, social service.